Myocarditis in a Traveler Returning from the Dominican Republic: An Unusual Presentation of Dengue Fever - Zea, Diego (The American Society of Tropical Medicine and Hygiene, 2014)
Myocarditis is an uncommon manifestation of dengue fever. We describe a case of a 69-year-old Hispanic male who presented to an emergency room in New York City 3 days after returning from a trip to the Dominican Republic complaining of a 1-day history of chest pain and fever. His first electrocardiogram showed a new left bundle branch block, and initial cardiac enzymes included troponin of 5 ng/dL, creatine kinase-MB of 9 ng/mL, and myoglobin of 234 ng/mL. Dengue fever antibodies were found to be elevated: immunoglobulin M (IgM) titer was 2.48 (reference range < 0.9), and immunoglobulin G (IgG) titer was 4.26 (reference range < 0.9). The patient was diagnosed with myocarditis caused by dengue fever. He improved after 1 week with conservative management in a telemetry unit and was discharged home.